Level of Critical Thinking among Academically Well-Achieved and Average Students at Mut’ah University - Shahin, Awni (Dirasat: Educational Sciences, 2022)
The current study aims to reveal the level of critical thinking among well-achieved and average students of the Department of Counseling and Special Education at Mutah University. A descriptive approach was followed and the study sample consisted of (116) undergraduate students from the Department of Counseling and Special Education, including (83) average students and (33) academically superior students. A multiple-choice objective test for critical thinking was developed, consisting of (34) items. The results indicate that the level of critical thinking among well-achieved students was average, while the level of critical thinking among average students was low. The differences were statistically significant among the levels of well-achieved students. The differences were not statistically significant among the students due to specialization (counseling, mental health, and special education) or school year (first, second, and third). One of the most important recommendations of the study is the need to develop training programs for critical thinking of students and to use teaching strategies based on dialogue, discussion and reasoning to develop critical thinking skills..